Implementasi SAK EMKM di UMKM Kab. Aceh Barat: Pengaruh Pendidikan, Business Size, dan Sosialisasi - Mustafira, Mustafira; Soufyan, Dara Angreka; Sari, Dewi Maya; Amri, Abrar; Risnafitri, Hafizhah; Mahdani, Rimal; Putri, Cut Widy Aulia (Universitas Teuku Umar, 2024)
MSMEs play a crucial role in Indonesia’s economy and have demonstrated resilience during the pandemic. However, despite the issuance of SAK EMKM to facilitate financial reporting for MSMEs, many MSMEs in Kabupaten Aceh Barat still lack a proper understanding of these standards. This research aims to analyze the influence of educational background, business size, and the provision of information and socialization on MSME actors’ understanding of SAK EMKM implementation. Using survey methods and multiple linear regression analysis, the results reveal that educational background and the provision of the information and socialization have significant impacts on MSME actors’ understanding. However, business size does not have a significant effect. These findings highlight the importance of more effective education and socialization for MSME actors to enhance their ability to prepare financial statements in accordance with the applicable standards.